2019
DOI: 10.1155/2019/2492097
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Wall Thickening Reported in Abdominal CT: Does It Always Imply Malignancy?

Abstract: Aim/Background. Early diagnosis of patients with colon cancer is one of the most important parameters affecting the survival of patients. In this study, we aimed to examine the effect of the age, hemoglobin (Hb), albumin, neutrophil lymphocyte ratio (NLR), thrombocyte lymphocyte ratio (PLR), and mean platelet values (MPV) on the separation of benign and malignant diseases in patients with suspected colon wall thickness (CWT) observed in abdominal computed tomography (CT) examination. Method. The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…There is no consensus regarding what constitutes MT on CT with some authors suggesting any perceptible thickening to indicate abnormalities [24,25]. Abnormalities are frequently incorrectly reported on CT if the part of the intestinal tract being examined is either collapsed or only partially distended.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus regarding what constitutes MT on CT with some authors suggesting any perceptible thickening to indicate abnormalities [24,25]. Abnormalities are frequently incorrectly reported on CT if the part of the intestinal tract being examined is either collapsed or only partially distended.…”
Section: Discussionmentioning
confidence: 99%
“…However, this accuracy level decreased to 26-53% in patients with the early stages of gastric malignancies. Also, Akbas et al noted that the antropyloric region was challenging to evaluate regarding increased wall thickness associated with gastric malignancies due to its anatomical and physiological characteristics [3]. The peristaltic movements in this region and the physiological thickness of the antral smooth muscle can be confounding.…”
Section: Discussionmentioning
confidence: 99%
“…One of these findings is the visceral wall thickening, either at the upper or lower gastrointestinal tract. While some incidental reports of wall thickening may represent normal findings, some minor changes could be an early sign of malignancy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Akbas et al retrospectively analyzed the colonoscopic evaluations of CWTs reported in aCT for any reason in their studies [ 17 ]. They have focused on hemoglobin, neutrophil-lymphocyte ratio (NLR), and mean platelet volume (MPV) of patients with CWT and contribute to the separation of benign and malignant pathologies.…”
Section: Discussionmentioning
confidence: 99%